Evaluation of a One-Step Serological Test for Lyme Disease - Kirsten Fagan; Marta Urban; P Rocco LaSala; Charles R Caso; James W Needham; Anu S Maharjan (The Journal of Applied Laboratory Medicine, 2026)
Abstract Background Lyme disease, a vector-borne zoonosis caused by Borrelia species, is classified into early localized and late disseminated infection. Left untreated, infected patients face multisystem pathology involving the joints, heart, and peripheral and central nervous system, making early antibiotic therapy essential. Lyme diagnosis with standard 2-tier test (STTT) and a modified 2-tier test utilize sequential serological assays. In this study, we evaluated the InBios Lyme Detect™ Multiplex ELISA (RUO) (InBios ELISA), a one-step method that combines screening and confirmatory tests. While a recent publication (Curr. Issues Mol. Biol. 2021;42:333–84.) demonstrated good performance of the InBios ELISA during early stages of Lyme disease, this study aimed to assess assay performance relative to STTT and to characterize IgG and IgM reactivity compared to standard immunoblot. Methods A convenience sampling of 119 residual sera previously characterized by STTT were analyzed for Lyme antibodies using the InBios ELISA. The evaluation quantified antigen reactivity using imaging and machine-learning analysis, which triggered simultaneous confirmatory analysis to provide an inclusive final interpretation. Results Among the 119 serum samples, InBios ELISA demonstrated 99.2% concordance with STTT. A single discordant result was observed for one STTT-positive sample with IgM confirmation. Concordance between second-tier immunoblots (IgM or IgG) and InBios IgM or IgG index was 76.2% for both. Conclusions This study shows that the InBios ELISA can (with minimal discordance) interpret both screen and confirmatory results in one step. Overall, there is a potential to replace the 2-tier test with one-step InBios ELISA to enable rapid turnaround and improve diagnosis of Lyme.